2010
DOI: 10.1103/physrevlett.104.137001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dirac Cone Electronic Dispersion inBaFe2As2

Abstract: We performed an angle-resolved photoemission spectroscopy study of BaFe2As2, which is the parent compound of the so-called 122 phase of the iron-pnictide high-temperature superconductors. We reveal the existence of a Dirac cone in the electronic structure of this material below the spin-density-wave temperature, which is responsible for small spots of high photoemission intensity at the Fermi level. Our analysis suggests that the cone is slightly anisotropic and its apex is located very near the Fermi level, l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
172
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 31 publications
45
172
0
Order By: Relevance
“…As we can see, the locations of the bright spots are around (k x , k y ) = ±(0.3π, 0.3π) and the equivalent symmetry points outside the MBZ, on the Γ-M line, in qualitative agreement with experiment. 11 In addition, although most parts of the original FSs around Γ are gapped by the SDW order, the gap value is extremely small on these FSs. Thus, around Γ, the low-energy spectral function has moderate intensity and this can be seen from the ring structure around Γ with lower intensity, as compared to those bright spots.…”
Section: Fermi Surface Topology In the Sdw Statementioning
confidence: 99%
See 2 more Smart Citations
“…As we can see, the locations of the bright spots are around (k x , k y ) = ±(0.3π, 0.3π) and the equivalent symmetry points outside the MBZ, on the Γ-M line, in qualitative agreement with experiment. 11 In addition, although most parts of the original FSs around Γ are gapped by the SDW order, the gap value is extremely small on these FSs. Thus, around Γ, the low-energy spectral function has moderate intensity and this can be seen from the ring structure around Γ with lower intensity, as compared to those bright spots.…”
Section: Fermi Surface Topology In the Sdw Statementioning
confidence: 99%
“…However, whether these FSs and Dirac cones are electron-or hole-like is within uncertainties of the experiment. 11 On the other hand, theoretically it was shown that in both a two-band model and a five-band model, nodes in the SDW gap function must exist due to the symmetryenforced degeneracy at the Γ and M high-symmetry points, even in the presence of perfect nesting, but the number and locations of these nodes are model dependant. 38 Therefore, whether they correspond to the experimentally observed Dirac cones is still unclear.…”
Section: Fermi Surface Topology In the Sdw Statementioning
confidence: 99%
See 1 more Smart Citation
“…From experiment, there are both pro and con arguments on this problem. Pro: any time when the FS nesting is good (BFA [29,50,52] and other parent compounds of 122 family [56][57][58], NaFeAs [70,71]), the SDW is present, and when nesting is poor or absent (superconducting BKFA [38,39], BFCA [28,45], BFAP [56], and stoichiometric LiFeAs [62]), there is no magnetic ordering. Con: Fe 1+y Te shows different spin order, see Fig.…”
Section: Magnetic Orderingmentioning
confidence: 99%
“…As a consequence of good crystal quality and variety of compounds, the 122 family is the most studied by ARPES [37] (see [38][39][40][41][42][43][44] for BKFA, [28,[45][46][47][48][49] for BFCA, [29,[50][51][52][53] for BFA, [31,54] for KFA, [29,55] for CaFe 2 As 2 , [56,57] for BFAP, [58] for EuFe 2 (As 1-x P x ) 2 ). The ARPES spectra well represent the bulk electronic structure of this family, at least, for the hole doped BKFA, BNFA, and BFAP, where the superconducting gap is routinely observed [39,41,59] and is in a good agreement with the bulk probes [43,44].…”
mentioning
confidence: 99%